PHYSICAL CULTURE IN ENSURING A HEALTHY LIFESTYLE - Shokirov Shukhrat Gayratovich; Najmiddinov Asrorjon Bakhriddin Ugli (Galaxy International Interdisciplinary Research Journal, 2023)
This article discusses the issues of forming a healthy lifestyle of the student through physical culture and self-education. A study was conducted to determine the deterioration of health among students during training.